UJI AKTIFITAS ENZIM SELULASE DAN LIGNINASE DARI BEBERAPA JAMUR DAN POTENSINYA SEBAGAI PENDUKUNG PERTUMBUHAN TANAMAN TERONG (Solarium melongena) - YB Subowo (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The objective of this study was to obtain effective and beneficial microorganism specially fungi, which are able to stimulate and increase eggplant growth. Four lignocellulolytic fungi Mucor sp. M13T, Aspergillus sp. M2P, Penicillium sp.M3P1, Penicillium sp. R 7.S and mixture of them) were evaluated for their ability to promote plant growth through provision of availability of soluble carbon finally stimulate beneficial microbial growth, and thus promoting eggplant growth. Aspergillus sp. M2P having cellulolytic activity (0.0612 U/ml) and Penicillium sp. M3P1 having ligninase capacity showing different plant growth stimulation on character and yield coefficient. Penicillium sp. M3P1 more effective to increase plant growth than that of control.While Aspergillus sp. M2P was less effective compared to Penicillium sp. M3P1. Therefore,we recommended using Penicillium sp. M3P1 as plant growth promoter for eggplant.",